Liver metastasis of endometrial stromal sarcoma - Ramia, Jose M (Baishideng Publishing Group Co., Limited, 2012)
Resection of liver metastases from gynaecological tumours is uncommon. Endometrial stromal sarcomas (ESS) are low incidence gynecological tumours which can originate in previous sites of endometriosis or following metaplasia of the pelvic peritoneal wall, and which are exceptionally associated with liver metastasis. We present a 68-year-old woman with a ESS and metachronic liver metastasis treated by liver resection. There is very little literature on clinical management about liver metastasis from ESS, but extrapolating the data obtained with liver metastasis from sarcomas and uterine tumours, we should recommend resection as this is considered a resectable extrauterine metastasis. In cases with more sites of extrauterine disease, liver resection should also be performed if the other sites are resectable.